GRAPE SEED (VITIS VINIFERA L.) ALLEVIATE REPRODUCTIVE TOXICITY CAUSED BY LINDANE IN NEW ZEELAND WHITE MALE RABBITS - Salma H. ABU HAFSA; Hassan A. AYMAN; Assadi Soumeh ELHAM; Agatha POPESCU; Dorina MOCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Natural dietary antioxidants are important for their ability to protect cells from miscellaneous damage. Grape seed (GS) (Vitis vinifera L., Vitacease) is a potent natural antioxidant. The present study aimed to investigate the protective effect of GS against the possible testicular dysfunction caused by Lindane in male rabbits. Eighty sexually mature NZW male rabbits (average BW: 2.150 ± 0.50 kg) were equally divided into four groups, the first served as negative control, the second received Lindane (L) (4 mg/kg body weight 1/ 50 LD 50), the third was supplemented with GS powder (50 g/kg diet), and the fourth received both Lindane and GS (LGS). Doses were given once daily via gavage for 90 consecutive days. The results revealed that, L group induced significant decrease in final body weight, sex organs relative weight, sperm concentration, motility and viability, serum testosterone concentration. Moreover, L altered the histological structure of the testis. Supplementation with GS ameliorated the harmful effects of L, this was also proved histopathologically by the noticeable improvement in the testis tissues. It may be concluded that GS may be promising as a natural therapeutic agent in Lindane -induced reproductive toxicity and oxidative stress in the male rabbit testes.